Perception of the Library by Secondary School Students in Enhancing Success in their Examinations: Myth or Reality? - Eghosa, Bosah L. (Richtmann Publishing, 2012)
In the early 20th century to the 1070s in this country, library utilization formed an indispensable arm in theteaching/learning process especially at the secondary school level.Sound graduates were produced as a result. Could the samebe said today of our graduates both at the secondary and tertiary levels of our school system? This research therefore wascarried out to investigate whether the library has become a myth in the attainment of success at the school certificate level. Onehypothesis was formulated to guide the study: â€œthe performances of secondary school students in their examination are notsignificantly influenced by the use of library servicesâ€ 200 outgone and present out-going SS III students (100 each) wereinvestigated. Hypothesis was tested by means of chi-square technique at the 0.5 level Hypothesis was accepted and it wasrecommended that the Nigerian Library Association should go beyond publications and conferences to meet with StateGovernors and Commissioner of education on how to set aside a considerable budget for the revamping of Library Education inNigeria.